1981
DOI: 10.1017/s0014479700011200
|View full text |Cite
|
Sign up to set email alerts
|

Dry Matter Production and Partition in Relation to Yield of Tea

Abstract: SUMMARYTea yields of 1 to 4 t ha−1y−1 of dry shoot tips are much less than those of other vegetative crops like grasslands or forests growing in similar conditions, partly because plucking restricts tea biomass production, but mainly because the harvest index of tea is small. In Kenya, plucked tea produced 36% less biomass per hectare per year than unplucked tea, and 64% less wood. Only 8·3% of the total annual biomass increment was harvested. This proportion might be increased by plucking older leaves, increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
5

Year Published

1985
1985
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 5 publications
5
26
5
Order By: Relevance
“…We found that the woody tissue that forms the tea bush frame always had the highest DM irrespective of age and genotype-density combinations, which has also been reported by Dang (2005), Magambo and Cannel (1981), Ng'etich and Stephens (2001) and Wachira and Ng'etich (1999). Unlike in forests and tree plantations where foliage and fine root biomass decreases with age and maturity (Claus and George 2005), clear differences in foliage DM between genotypes/cultivars did exist in this study.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We found that the woody tissue that forms the tea bush frame always had the highest DM irrespective of age and genotype-density combinations, which has also been reported by Dang (2005), Magambo and Cannel (1981), Ng'etich and Stephens (2001) and Wachira and Ng'etich (1999). Unlike in forests and tree plantations where foliage and fine root biomass decreases with age and maturity (Claus and George 2005), clear differences in foliage DM between genotypes/cultivars did exist in this study.…”
Section: Discussionsupporting
confidence: 85%
“…Management of the tea bush by periodical pruning and constant removal of the apical buds and breakingback to maintain the plucking table had been suggested as the main reason for the low DM. Indeed, Magambo and Cannel (1981) attributed the low standing DM of tea compared to forest trees and C 3 vegetative crops as due to the continual plucking that limits the amount of young photosynthetically active leaves as well as assimilate supply to other plant organs. Instead of standing biomass, the rate of DM increase per year would be a better indicator for the productivity of tea plantations.…”
Section: Discussionmentioning
confidence: 99%
“…Usually young shoots, a small portion of the tea plant,14 are harvested at regular intervals for processing teas. As a recommended practice, shoots with two leaves and a bud are harvested 15.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research demonstrated wide response ranges among tea genotypes to different environments (Carr, 1997;Obaga et al, 1988;Tanton, 1982a;Wickremaratne, 1981;Carr and Stephens, 1992). Indeed, dry matter partitioning (Ng'etich and Stephenes, 2001a;Magambo and Canell, 1981;Magambo and Waithaka, 1983) and quality (Owuor et al, 2010b) of tea vary with clones and location of production. However, different clones have varying abilities to absorb nutrients from the soil (Yemane et al, 2008;Wanyoko, 1981) leading to clonal variation in mature leaf nutrient levels (Wanyoko and Njuguna, 1983).…”
Section: Resultsmentioning
confidence: 99%